(3UahI GdUaGJ aj TQM OYGA GdSeGJs - (3EHQGgje Hf Ydj Hf GdMSf GdMGQKj GdYGedj GdcaYej, Jbj GdOjf,J (B905 (3g` s ((3eMeO WGgQ GdSeGhj s)
(3ChdgG (B:s
(3CeG HYO abO CeQ ef EPG PcQJ GdCdaGX GdQhGFY hGdYdeGA GdHhGY hGdNWHGA GdeUGbY s
(3BNQgG (B:s
(3hSghI HfGf ChTOhgG aJdc YGOI NdUGA Bejf jGQH GdYGdejf s
(3HChdg agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B53 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B65s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B68s
Keywords: (3GdJUha hGdBOGH GdTQYjIs